Vehicle collision on bridge piers – static and dynamic elasto-plastic analysis a comparative study - Joshi, A.S.; Gupta, L.M. (Journal of Structural Engineering, 2024)
Bridge piers are subjected to vehicle collision force. This is primarily due to overcrowding of vehicles, encroached spaces and lesser margin around piers. The present study is focused on the effect of a colliding vehicle on predefined geometries of pier. The parametric study is intended to investigate the plasticity induced in a pier due to a colliding vehicle. The piers are analyzed using Finite element method. The collision force is necessarily a dynamic one; however in customary design the specifications worldwide advocate the use of static force. Both, the dynamic and the static forces are applied and the results presented. The forces considered for static analysis are based on specifications of several countries while the force-time histories adopted for transient-elasto-plastic responses of the pier are adopted from simulated crash test results. A range of results in the form of graphs is presented. The elasto-plastic response of the pier is sought, for which the Drucker-Prager yield criterion which is suitable for concrete is adopted.